The surname structure of Trentino (Italy) and its relationship with dialects and genes - Alessio Boattini; Eugenio Bortolini; Roland Bauer; Marta Ottone; Rossella Miglio; Paola Gueresi; Davide Pettener (Taylor & Francis Group, 2021)
Background Thanks to the availability of rich surname, linguistic and genetic information, together with its geographic and cultural complexity, Trentino (North-Eastern Italy) is an ideal place to test the relationships between genetic and cultural traits. Aim We provide a comprehensive study of population structures based on surname and dialect variability and evaluate their relationships with genetic diversity in Trentino. Subjects and methods Surname data were collected for 363 parishes, linguistic data for 57 dialects and genetic data for different sets of molecular markers (Y-chromosome, mtDNA, autosomal) in 10 populations. Analyses relied on different multivariate methods and correlation tests. Results Besides the expected isolation-by-distance-like patterns (with few local exceptions, likely related to sociocultural instances), we detected a significant and geography-independent association between dialects and surnames. As for molecular markers, only Y-chromosomal STRs seem to be associated with the dialects, although no significant result was obtained. No evidence for correlation between molecular markers and surnames was observed. Conclusion Surnames act as cultural markers as do other words, although in this context they cannot be used as reliable proxies for genetic variability at a local scale.